Assessing the satisfaction of students with the learning methods used during the coronavirus pandemic in Saudi Universities - Khaleel I Alyahya; Ahmed Fathalla Ibrahim El Fouhil (Journal of Nature and Science of Medicine, 2022)
Objectives: The aim was to assess Saudi students' satisfaction with two methods of lecture delivery used during coronavirus pandemic, namely live online sessions (LOS) and recorded online lectures (ROL), and students' perspectives regarding distance and traditional education. Materials and Methods: A cross-sectional study was conducted on 600 Saudi students from 22 Saudi universities during December 2020. A questionnaire, formed of both multiple choices and open-ended questions, was designed at the Department of Anatomy, College of Medicine, Riyadh, Saudi Arabia, and distributed via social media applications. Collected data were statistically analyzed. Results: Participants were satisfied with both methods and recommended to implement both of them. They had better outcomes with ROL, felt it more appropriate for preparation for exams, and for enhancement of focus ability. Students of health and sciences colleges had more preference of LOS regarding satisfaction and implementation, and of ROL for preparation for examinations and enhancement of focus ability. Students of humanities colleges preferred ROL in all aspects. Being time saving and giving more flexibility for learners, students suggested implementation of distance learning for selected theoretical courses. Using better technologies for communication and training teachers and students on ways to use educational programs is recommended. Traditional practical classes should be small, more interactive, recorded, and available on website. Conclusion: Students were satisfied with both methods with more preference of one of them in some aspects and suggested continuous innovation in learning.